The Hazareshwar Temple - Temples of India Project Team (Jio Institute, 2024)
The Hazareshwar Temple is comparatively a small temple in the Bijolia temple complex which comprises a mandapa (pillared hall), a shallow antarala (vestibule or antechamber), and a garbhagriha (sanctorum). It rests upon a deeply set vedibandha (basal mouldings), upon which the jangha (wall) is situated, supporting the shikhara (superstructure). Dedicated to Shiva, the Hazareshwar Temple is noted by the Archaeological Survey of India (ASI) for its architectural style resembling Bhumija (earth-born) architecture. An inscription discovered within the temple's mandapa indicates its dedication to Pashupata Shaivism.